Neuroanatomy an illustrated colour text - Crossman, A. R.; Neary, David (Professor of neurology) (Churchill Livingstone, 2015)
Now fully revised and updated, this leading ICT series volume offers concise, superbly illustrated coverage of neuroanatomy that throughout makes clear the relevance of the anatomy to the practice of modern clinical neurology. Building on the huge success of previous editions, Neuroanatomy ICT, fifth edition is designed and written primarily with the medical student in mind, although it will again be valued by the range of other students and professionals who need a clear, current understanding of this important area. Minimum assumptions are made of existing knowledge of the subject.